PENGELOLAAN LINGKUNGAN CEKAMAN SALIN UNTUK MENINGKATKAN HASIL PADI - Tita Rustiati; Zuziana Susanti; Zaqiah M Hikmah; Ade Ruskandar (Agroswagati Jurnal Agronomi, 2020)
Management of the environment which is gripped by saline is very necessary to increase the yield of rice. The research was carried out in the farmers' land of Indramayu-West Java district in February - July 2019 using a split plot design with 3 replications. The variety used is Inpari 34. The treatment is gypsum dossage and organic matter. The results showed that the management of saline environmental stress by giving gypsum and organic matter did not affect plant growth including the number of tillers, leaf greenness value and yield on rice. Gypsum 1 ton/ha will provide maximum results 2,375 tons/ha dried grain if accompanied by the provision of 4 tons of organic matter/ha. Gypsum 1 ton/ha with organic matter more than 4 tons/ha will reduce rice yield. Gypsum application of 3 tons / ha reaches 2,6792 tons ha without the provision of organic matter.